Development of Cd-doped Co Nanoparticles Encapsulated in Graphite Shell as Novel Electrode Material for the Capacitive Deionization Technology - Barakat, Nasser A. M.; Khalil, Khalil Abdelrazek; El-Deen, Ahmad G.; Kim, Hakyong (Nano-Micro Letters, 2013)
Because of the low energy requirement and the environmentally safe byproducts, the capacitive deionization water desalination technology has attracted the attention of many researchers. The important requirements for electrode materials are good electrical conductivity, high surface area, good chemical stability and high specific capacitance. In this study, metallic nanoparticles that are encapsulated in a graphite shell (Cd-doped Co/C NPs) are introduced as the new electrode material for the capacitive deionization process because they have higher specific capacitance than the pristine carbonaceous materials. Cd-doped Co/C NPs perform better than graphene and the activated carbon. The introduced nanoparticles were synthesized using a simple sol-gel technique. A typical sol-gel composed of cadmium acetate, cobalt acetate and poly(vinyl alcohol) was prepared based on the polycondensation property of the acetates. The physiochemical characterizations that were used confirmed that the drying, grinding and calcination in an Ar atmosphere of the prepared gel produced the Cd-doped Co nanoparticles, which were encapsulated in a thin graphite layer. Overall, the present study suggests a new method to effectively use the encapsulated bimetallic nanostructures in the capacitive deionization technology.